Predicting Functional Outcome after Stroke: The Influence of Neglect on Basic Activities in Daily Living - Nijboer, Tanja; Van de Port, Ingrid; Schepers, Vera; Post, Marcel; Visser-Meily, Anne (Frontiers in Human Neuroscience, 2013)
One prominent deficit resulting from stroke is visuo-spatial neglect, which has been associated with slower and more attenuated recovery patterns of sensory-motor impairment as well as limitations in activities of daily living. The aim of the current study was to further specify the relationship between neglect and recovery of different domains of ADL. 184 Patients were assessed with the Functional Independence Measure (FIM) in the first week of inpatient rehabilitation, and again at 6, 12, and 36 months post-stroke. On average, neglect patients scored significantly lower on Self-care, Transfers and Locomotion compared to non-neglect patients, but these differences became smaller with progress of time. Overall, no differences between groups were found for Sphincter control and Cognition. Patients with more severe neglect scored significantly lower on Self-care and Transfers compared to patients with mild neglect. In conclusion, even though time-dependent recovery takes place, neglect patients remain more dependent when it comes to Self-care. During rehabilitation, it would be of importance to test for independence in ADL domains in neglect in order to define realistic treatment goals. The current findings could be taken into account in early multidisciplinary intervention planning in the sub-acute phase, to optimise regaining ADL.